Validation and perspectives of the Russian version of the quality of life questionnaire in patients with diabetic peripheral polyneuropathy - Elena Yurievna Komelyagina; Mikhail Borisovich Antsiferov; Olga Mikhailovna Uvarova (Сахарный диабет)
Background. Quality of life is a multivariate indicator of patient?s perception of various aspects of his/her own life. Questionnaires (specific and non-specific) are used to assess it. Objective. . To validate the Russian version of the specific quality of life questionnaire ?NeuroQol? in diabetic patients with peripheral polyneuropathy. Materials and Methods. A total of 371 diabetic patients participated in the study. All patients were screened for the signs of peripheral neuropathy and limb ischemia. The examination results were used to evaluate the eligibility of a patient; the eligible patients were then asked to fill in the quality of life questionnaire. The validation included translation, pilot testing and assessment of reliability and validity. Results. Cronbach?s alpha coefficient of internal consistency exceeded 0.8 in all scales and proved the high reliability of the questionnaire. Criterion validity was analyzed by Spearmen correlation (r) coefficient between the domains and external parameters. The results obtained revealed significant correlation between NeuroQol domains and neuropathy severity, which indicates adequate criterion validity. The psychometric assessment (construct validity) was performed using factor analysis. The physical and psychosocial factors contributing to the quality of life were identified; they confirmed the validity of the questionnaire structure. Conclusion. The results demonstrate that the Russian version of the NeuroQol questionnaire is valid and reliable. This questionnaire enables one to assess quality of life in patients with the signs of peripheral diabetic polyneuropathy, including evaluation of the efficiency of various treatment strategies for complications. The lack of social life and psychological conditions of patients affect their quality of life more than physical complications do. These parameters must become the focus of specialists' attention in their efforts to improve the quality of life in this category of patients.